Analisis Efektifitas Sentra Penegakan Hukum Terpadu (Gakkumdu) dalam Penegakan Pidana Pemilu Tahun 2024 di Jawa Tengah berdasarkan Asas Kepastian Hukum - Rahmat, Diding; Sudarto, Sudarto; Riwanto, Agus (Neolectura, 2024)
This study aims to analyze and examine the effectiveness of the Integrated Law Enforcement Center (Gakkumdu) in criminal enforcement of the 2024 Election in Central Java. This type of research is empirical or non-doctrinal law, the nature of analytical descriptive research. Using a qualitative approach with primary data from interviews and observations. Secondary data from books, scientific journal articles and legislative review. The results of the study show that the Central Java Gakkumdu Center has carried out its functions and authorities as a center for criminal law enforcement activities in accordance with the Election Law and Perbawaslu, but it has not been effective and legally certain. Because in handling election crime cases in 35 districts/cities as many as 110 cases, only 5 cases have permanent legal force, 2 cases stopped at the Police investigation, and 103 cases stopped at the discussion of the Gakkumdu Center. The causal factors are not in accordance with the theory of the legal system of law: (1) Legal substance: (a) the time to handle the case of election crimes is short (Speedy trial), (b) the legal subject of the perpetrator of the election crime is not fulfilled, (c) lack of evidence in the investigation of election crimes, and (d) difficulties in finding witnesses in the investigation of election crimes. (2) Legal structure: (a) many institutions in the Gakkumdu Center make coordination difficult, (b) different perceptions between institutions in the Gakkumdu Center make it difficult to determine election crimes, (c) the Gakkumdu Center is a non-institutional coordination forum in election crime enforcement, (d) the election crime enforcement coordinator Bawaslu only forwards reports and not as an election crime investigator. (3) Legal culture: (a) lack of understanding of election crime violations, (b) lack of public awareness of reporting election crimes to the gakkumdu center, (c) lack of public willingness to witness election crime cases, and (d) weak legal awareness of election participants to comply with the election law. The solutions to overcome the ineffectiveness of the Gakkumdu Center in election crime enforcement in the future: (a) the need for a single institution in election crime enforcement, and (b) the strengthening of Bawaslu's authority in election crime enforcement